Penyuluhan Literasi Media: Sosialisasi Cara Cerdas Menggunakan Media Informasi dalam Menanggulangi Disinformasi tentang Vaksin Covid-19 di Desa Karangrau - Ikhwan Yuda Kusuma; Galih Samodra; Halimatu Sa'diah (Yayasan Inspirasi El Burhani, 2022)
Introduction: Coronavirus is an RNA virus with a particle size of 120-160 nm. This virus mainly infects animals, including bats and camels. Before the widespread coronavirus outbreak, it was known that there were 6 types of coronavirus that could infect humans, namely alphacoronavirus 229E, alphacoronavirus NL63, betacoronavirus OC43, betacoronavirus HKU1, Severe Acute Respiratory Illness Coronavirus (SARS-CoV), and Middle East Respiratory Syndrome Coronavirus (MERS-CoV). The level of public knowledge related to the Coronavirus in Indonesia is still relatively low, therefore it is necessary to carry out socialization on Smart Ways to Use Information Media in Overcoming Disinformation About the COVID-19 Vaccine. Objective: The purpose of implementing this community service activity (PKM) is to provide information to the public regarding the importance of filtering incoming information so that it does not lead to wrong assumptions or disinformation, especially the issue of the COVID-19 vaccine so that people are not easily fooled and absorb facts well. Method : This counseling is done by lecture method using posters and leaflets. Result: The pre-test which was carried out before the delivery of the material showed the results of 52.33 ± 12.30% and after the delivery of the material followed by the post-test the results were 75.00 ± 17.08%. Conclusion: The counseling participants consisting of 30 respondents from various ages and occupations were able to understand the vaccines for handling COVID-19 that were delivered.